Health Promotion at School - Knisel, Elke (De Gruyter, 2019)
For decades the health of children and adolescents has been a topic of interest in all parts of Europe. And there is quite a consensus that schools are the most appropriate setting to promote health. Childhood and adolescence constitute key stages for learning and adopting a health-related and active lifestyle which includes physical activity and sports. The book describes a new approach to enhance students` health awareness through experimental learning settings in P.E. class, cross-subject teaching, and project work.Teaching health topics requires a pedagogical and didactical framework based on the concept of health literacy and interdisciplinary research discussed by the authors. Teaching examples to improve students` health knowledge, health competencies and skills as well as health behaviour and habits at school implicates a new teaching structure presented in the book.